Employing Adaptt Tool to respond to the rising COVID-19 caseload in the European region - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Medicine Science, 2020)
The Corona Virus Disease-2019 (COVID-19) pandemic continues its ascent in terms of the reported cases, the number of deaths and the geographical distribution. In an attempt to improve the preparedness activities and national response plan, the European region has designed an Adaptt tool, which can assist the program managers and hospital authorities to enhance the capacity for extending quality-assured inpatient care. This enhancement can be with regard to identifying the number of beds required for providing care for different categories of patients. The recommendations for enhancing the capacity of the hospital to meet the requirement of providing acute and intensive care broadly targets four domains, namely staff, premises, supplies and finally the system. In conclusion, the Adaptt tool developed in the European region is an effective strategy to respond to the challenge of the sudden upsurge in the number of COVID-19 cases and thereby improve our preparedness level and response to the detected cases. [Med-Science 2020; 9(2.000): 524-5]